Green Investment, Green Innovation, and Firm Value: Moderating Role of Profitability - Syifa Auliana Wulandari; Mardiyani Mardiyani (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
Firm value is an indicator of a company's performance. Sustainability issues and environmental demands pose challenges for companies, therefore, strategies are needed that can strengthen the company’s competitiveness and increas the firm value in the long term. This study aims to analyze the role of profitability as a moderating variable in the relationship between green investment, green innovation, and firm value. The methode used in this research is a quantitative approach. The sampling technique was carried out using purposive sampling, resulting in 15 companies as the research sample. Data analysis was performed using Moderated Regression Analysis (MRA) in STATA version 17. The results of the study based on the Random Effect Model show that green investment has a negative effect on firm value, that green innovation has no effect on firm value, and that profitability does not moderate the relationship between green innovation and firm value. However, green investment moderated by profitability has a significant positive effect on firm value. Green activities will run more optimally if supported by optimal financial performance. Allocating resources effectively to support green initiatives can enhance a company's reputation, increase investor interest, and create sustainable value.